Paciente femenino de 34 años de edad que presenta anorexia nerviosa. - Galarza Roldán, María Del Carmen (2020)
At present in Ecuador there are no exact figures on this disease, however the results are that in Cuenca there are 15% of women who suffer from these eating problems. It is estimated that three out of 5 people have bulimia and anorexia. In the western countries, a prevalence of 1% for anorexia nervosa and 2 to 4% for bulimia nervosa is estimated, the prevalence of atypical eating disorders can be around 5 and 10%, although the data in men they are more limited, a prevalence among men and women of 9.1% is stimulated. Female patient of 22 years of age, attends the consultation accompanied by her parents and her sister, they describe that 8 months ago she began asking her mother to cook healthy, because she began to lose weight, but everything began to change since He lost his son, in which he began to reduce food intake and skip several meals, is obsessed with the calories he eats. Roxana says he will be taking 800 kcal / day. For 2 months the intake has been reduced to an apple and water, has lost about 11kg (from 68 kg to 52kg), Amenorrhea for 4 months. Parents do not report purgative behaviors or exercise. Anorexia is a disease with more frequency in adolescents and young people but it can also appear after 40 years of age, the ideal of a slender and thin person that is observed in models and in fashion and social pressure especially in children. media, the terror of obesity and improper diets without control can be that you get a very serious disease that ends in death.